PENGEMBANGAN E-BOOKLET JENIS-JENIS BRYOPHYTA DI TEPIAN SUNGAI DESA MAWANGI SEBAGAI BAHAN AJAR TAMBAHAN MATERI BRYOPHYTA - Maulida, Rahmah; Amintarti, Sri (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
The lack of local potential-based teaching resources makes it challenging for students to grasp the Bryophyta subject, necessitating the development of e-booklet materials. The purpose of this study is to describe the types of moss on the banks of the Mawangi Village river and describe the approriateness, feasibility, readability, and effectiveness of the developed e-booklet. The e-booklet was developed adopting the 4D model technique (Define, Design, Develop, and Disseminate), however, is was only developed to the limited distribution stage in this study. Two Biology Education FKIP ULM lecturers and a Biology teacher from SMAN 1 Kandangan participated in the suitability and feasibility tests. Nine students participated in the readability test, while seventeen students participated in the effectiveness test. According to the study’s results, 8 types of Bryophyta were found on the banks of the Mawangi Village River, Hulu Sungai Selatan Regency, including Ectropothecium sp., Fissidens sp., Calymperes sp., Octoblepharum sp., Thuidium sp., Bryum sp., Riccia sp., and Anthoceros sp. The e-booklet had an average approriateness test score of 4.19 (approriate), a feasibility test score of 4.36 (very feasible), a readibility test score of 4.53 (very good), and effectiveness test N-gain score of 0.72 (high). As a result, the e-booklet Types of Bryophyta on the Riverbanks of Mawangi Village is considered suitable for use as additional biology teaching material for high school students in grade X. Kata Kunci:Bahan ajar, bryophyta, e-booklet, pengembangan model 4D, tepian sungai Desa Mawangi